2010
DOI: 10.1111/j.1651-2227.2010.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinumtoxin A treatment in toddlers with cerebral palsy

Abstract: Early treatment of BoNT-A in children with spastic CP may decrease muscle tone and decelerate contracture development after 3.5 years. The effect on gait development remains inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 28 publications
1
62
0
5
Order By: Relevance
“…In previous studies, the effects of BTA treatment were estimated by the follow-up of active and passive movements of the joints on affected limbs as objective parameters [16][17][18][19][20] . However, we question the objectivity of such measurement, particularly active movement in younger children (the study sample), mainly due to the poor cooperation with the child during the examination.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the effects of BTA treatment were estimated by the follow-up of active and passive movements of the joints on affected limbs as objective parameters [16][17][18][19][20] . However, we question the objectivity of such measurement, particularly active movement in younger children (the study sample), mainly due to the poor cooperation with the child during the examination.…”
Section: Discussionmentioning
confidence: 99%
“…В наблюдениях K. Tedroff и соавт. [61] и C. A. Olesch и соавт. [62] -это легкие и самостоятель-но разрешающиеся симптомы: сыпь, слабость сгибате-лей пальцев, боль в месте инъекции.…”
Section: влияние ботулинотерапии на развитие ортопедических осложнениunclassified
“…В первом систематическом обзоре исследований ботулинотерапии у детей в возрасте до 2 лет был пред-ставлен анализ 299 работ, показавший эффективность использования данного метода для снижения спастично-сти, профилактики контрактур и отсрочки хирургического вмешательства. При этом лишь 3 работы имели дизайн рандомизированных контролируемых исследований и показали эффективность включения ранних инъекций БТА в комплексную реабилитацию детей самой младшей группы (64 ребенка в возрасте от 11 мес) [61][62][63]. Эти исследования продемонстрировали снижение спастич-ности как в мышцах верхних, так и нижних конечностей и сохранение положительных результатов реабилитации в ближайшие (12 мес) и отдаленные (3,5 года) сроки наблюдения, что соответствовало результатам исследо-ваний у детей старшей возрастной группы.…”
Section: Introductionunclassified
“…Three studies showed no effect. The study by Tedroff et al 4 was non-blinded with unmatched groups and the statistically significant effects were of unlikely clinical significance. Hawamdeh et al 2 claimed long-term benefit but the results were assessed by a non-blinded assessor and the magnitude of effect unlikely to be of clinical significance.…”
Section: Commentarymentioning
confidence: 99%